Effect of Hematologic Values in Determining the Resolution of Subacute Thyroiditis and Long-Term Hypothyroidism Risk - Savas Karatas; Burcu Hacıoğlu; Gökhan Kalaycı (Medical Laboratory Technology Journal, 2022)
Subacute thyroiditis (SAT), which can be considered a disease with infectious signs and parameters, can affect humans and lead to permanent hypothyroidism. Haematological parameters play an essential role in SAT; these parameters begin to normalise after the thyrotoxic phase; however, there is still a gap in knowledge about how these parameters play a role in SAT prognosis. Therefore, we wanted to investigate haematological parameters and their impact on treatment response and recovery phase in patients with SAT. 51 SAT patients and 44 healthy controls were included in the study. ESR, CRP, NLR and MPV were recorded at the diagnosis and after resolution. The changes in these parameters were compared to determine the resolution phase. The ratio of permanent hypothyroidism after one year was studied, and its relevance with these parameters at the time of diagnosis was explored. 36 of 51 SAT patients were female in the study (70.5%). The mean age was 45.53 ± 11.46 years. In the acute phase, WBC, Neutrophil, platelet, ESR, N/L, and P/L were significantly higher (p<0.05). In the recovery phase, MPV and lymphocyte count were significantly higher (p: 0.002 and p=0.002). WBC, CRP, and ESR had the highest AUC values in ROC analysis (0.990, 0.959, 0.907, p<0.05). P/L and N/L ratios also had higher ratios for the acute phase (0.807, 0.98, p<0.05, respectively). Δ ESR, Δ CRP, Δ N/L, and Δ P/L had the highest AUC for the recovery phase (AUC= 0.990, 0.899, 0889,0.800, p<0.5, respectively). Permanent hypothyroidism after one year was 9/42 (21.4%). In addition to ESR and CRP, NLR, PLR and MPV were also successfully used to estimate SAT activity and response to treatment. Moreover, a decrease in NLR and PLR and an increase in MPV were associated with the treatment response and resolution phase. However, these parameters did not determine the long-term risk of hypothyroidism.